The media portrayal of Arab Spring in newspaper editorials : the case of Pakistani The News International and Saudi Arabian Arab News - Afzal, Naeem (2017)
Editorials are often viewed as the mouthpiece of newspapers which reveal embedded elements such as social and cultural contexts, background of editorial writers and ideological beliefs of a newspaper in a society. Readers not only communicate with the editorials, but the former also interpret them subjectively. Yet, not much is known about how the media content is produced. Given that the Arab Spring has not been fully examined in the editorials, this study explores how editorials of mainstream English language newspapers in Pakistan and Saudi Arabia portray the uprising. Using a critical discourse analysis approach, the study examines the voice of a non-Arab (Pakistani) newspaper, The News International, and an Arab (Saudi) newspaper, Arab News, with a view to understand the Arab Spring. Data for this qualitative study consist of fourty-eight editorials collected, during the period of high media coverage of the Arab Spring, from January 2011 to December 2012. The data are analysed based on van Dijk‘s concepts of schematic categories of editorials, ideological square and rhetorical devices utilised in the media discourse and the three modes of persuasion, namely, ethos, pathos and logos. The findings reveal that the editorial writers in both newspapers positively portray the Arab Spring as a movement of 'change‘. The writers oppose the authorities in the affected countries through negative other-representation (them) and favour the protesters, who demanded change, through positive self-representation (us). The study also reveals how the newspaper rhetoric shares the protesters‘ emotions and justifies their demands to remove the dictatorial regimes. As a conclusion, the study contributes to the critical understanding of how newspaper editorials can (dis)empower the readers through the use of carefully constructed discourse.